Natural tourism development strategy in Murung Raya Regency, Central Kalimantan - I Dewa Gde Satrya; Joesarues (Tourism and Hospitality International Journal, 2022)
Tourism is one of the sectors that contribute greatly to the Indonesian economy, it will be beneficial for us if we can use all the existing tourism potentials to the fullest. Murung Raya has a very rich nature, making it a great natural tourism potential. This great resource will be useful if we know how to develop it in such a way as to benefit the region. The purpose of this study was to describe the strategy for developing nature tourism in Murung Raya Regency. This research uses a qualitative approach with case study research, data collection methods through interviews, observation, and secondary data. This research involves Penta helix informants from the government, community, business actors, media, and academia. The results of the findings of this study produce short-term, medium-term, and long-term strategies.